2D range modulator for high-precision water calorimetry in scanned carbon-ion beams - Holm, Kim Marina; Weber, Ulrich; Simeonov, Yuri; Krauss, Achim; Jäkel, Oliver; Greilich, Steffen (Physics in medicine and biology, 2020)
Ionization chamber-based dosimetry for carbon-ion beams still shows a significantly higher standard uncertainty than high-energy photon dosimetry. This is mainly caused by the high standard uncertainty of the correction factor for beam quality . Due to a lack of experimental data, the given values for are based on theoretical calculations. To reduce this standard uncertainty, factors for different irradiation conditions and ionization chambers (ICs) can be determined experimentally by means of water calorimetry. To perform such measurements in a spread-out Bragg peak (SOBP) for a scanned carbon-ion beam, we describe the process of creating an almost cubic dose distribution of about 6 × 6 × 6 cm3 using a 2D range modulator. The aim is to achieve a field homogeneity with a standard deviation of measured dose values in the middle of the SOBP (over a lateral range and a depth of about 4 cm) below 2% within a scanning time of under 100 s, applying a dose larger than 1 Gy. This paper describes the optimization and characterization of the dose distribution in detail.
Gesehen am 26.11.2020